Flood Storage Capacity Analysis Of Batang Mahat River For Dam Plan At Gunung Malintang Sub-District - Sari, Ridha; Asnur, Hanifah; Yunita, Rini (Universitas Andalas, 2025)
Gunung Malintang Sub-district is the largest Sub-district in Pangkalan Koto Baru District, Lima Puluh Kota Regency, West Sumatera Province. With an area of 249.43 km2, Kenagarian Gunung Malintang occupied 35.03 % of Pangkalan Koto Baru District’s total area. Crossing by a major river, Batang Mahat river, made this area hit by floods frequently which brings loss to the local community. Building dams is one of the solution for controlling the flood problems. As we know, dams could be a storage for the excessive water during floods, and it could also be a water resource during the dry season. For the reasons mentioned above, it is necessary to analyze the flood area on the location where the dams would build. The aim of this research is to calculate the discharge of probable flood (flood routing) using Muskingum method,and to estimate the storage capacity of the basin on the proposed construction site using relationship curve between elevations – storage area – storage volume. From the flood routing calculation of the probable flood for 100 year of return period, the inflow discharge 325,0911 m3/s and the outflow discharge is 165,6724 m3/s. The peak flood discharge occured at 3 rd hour. So the probable storage balance based on inflow – outflow discharge is 13,773,771.82 m3 in volume. From the storage capacity determination, using topographic analysis obtained 4.467.693,43 m2 in storage area and 30.213.084,779 m3 for storage volume. The dead storage capacity placed on the elevation +156 m above msl. The conclusions of the study indicates that the dead storage capacity meets the probable storage balance from flood routing. Which means that the design dam could be constructed at the elevation +156 m.